METHODOLOGICAL FOUNDATIONS OF THE ORGANIZATION SPECIALIZED PHARMACEUTICAL CARE FOR PATIENTS WITH SOCIALLY SIGNIFICANT DISEASES - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Филимонов, Сергей Николаевич; Семенихин, Виктор Андреевич (Medicine in Kuzbass, 2025)
Kemerovo State Medical University, Kemerovo, Russia, Scientific Research Institute of Complex Problems of Hygiene and occupational Diseases, Novokuznetsk, Russia The article presents a methodology for the study of the system of specialized pharmaceutical care (SРС) for patients with socially significant diseases based on a systematic approach. A logical and semantic model of the subject components of the formation of specialized pharmaceutical care for patients with socially significant diseases is constructed. The aim of the study the influence of subject components on the formation of specialized pharmaceutical care for patients with socially significant diseases. Materials and methods. The systematic approach involves identifying the composition of the system, its structure, functions, systemic factors and mechanisms, communication with the external environment, and its history. In this sense, the representative of the system in scientific research is the model of the subject components of specialized pharmaceutical care for patients with socially significant diseases. According to the definition, the model represents a mentally and materially realized system that reflects or reproduces the object of research, presents new information. The results and their discussion. In modern conditions, the development of a system of specialized pharmaceutical care for patients with socially significant diseases involves the influence of various factors and subject components of the formation of SРС in socially significant diseases, in particular cancer and HIV infection. The need to improve the quality of SРС in socially significant diseases requires the need to take into account the territorial and sectoral characteristics of the regions, their climatic and geographical factors, the variety of departmental relations, the transition to new forms of SРС provision, which was the justification for the application of the method of system analysis and modeling to the management process of JSC SРС organization. Conclusion. he presented semantic model is the basis for the development of a research methodology and a conceptual model for the provision of SРС in socially significant diseases at the territorial level. The methodology includes the definition of the purpose, principles, criteria, objects, research methods, results, theoretical and practical significance of applied research directions, depending on the stages of providing SРС in socially significant diseases.